DETERMINAN BELANJA MODAL PADA KABUPATEN DAN KOTA PROVINSI SULAWESI UTARA - Iis Dewi Herawati; Nisa Lestari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
Regional autonomy accommodates regions to carry out regional management in accordance with the needs and priorities set in the current year in all aspects, both physical and non-physical. This makes financial management in the public sector which includes regional revenues and expenditures must be carefully calculated, in addition to local governments also must be able to find sources to fund all needs in the region. Capital Expenditure is an element of the regional budget that is needed and is intended for the revitalization of facilities and infrastructure as well as infrastructure in the region. Revitalization and optimization are expected to occur optimally to achieve more excellent public services in a broad scope, so that effective and efficient governance can take place. This study aims to determine the determinants or factors that affect Capital Expenditures in districts/cities North Sulawesi Province for the 2015-2019 period. Based on the results, it is known that PAD and DAK have a positive effect on capital expenditure, while DAU has a negative effect. The simultaneous effect shows that all variables, namely PAD, DAU and DAK, have positive implications for Capital Expenditures in districts/cities North Sulawesi Province for the 2015-2019 period.